(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
The Teaching Assistance Program at the Faculty of Teacher Training and Education has an important role in preparing students to become professional and competent teachers. This study aims to analyze the effectiveness of the program in improving student teaching readiness. The approach used is qualitative with a descriptive-analytical method. Data was collected through in-depth interviews, observations, and documentation. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the Teaching Assistance Program provides significant hands-on experience for students in managing classes, developing learning plans, and interacting with students. Factors supporting the success of the program include the guidance of senior teachers, the support of partner schools, student motivation, and their involvement in curriculum management. Based on these findings, it is recommended that the quality of guidance be improved, cooperation with partner schools is strengthened, and program evaluations are carried out periodically. Thus, this program can run more optimally in preparing competent teacher candidates.